Genome-Wide Identification of a Regulatory Mutation in BMP15 Controlling Prolificacy in Sheep - Chantepie, Louise; Bodin, Loys; Sarry, Julien; Woloszyn, Florent; Plisson-Petit, Florence; Ruesche, Julien; Drouilhet, Laurence; Fabre, Stéphane (Frontiers in Genetics, 2020)
The search for the genetic determinism of prolificacy variability in sheep has evidenced several major mutations in genes playing a crucial role in the control of ovulation rate. In the Noire du Velay (NV) sheep population, a recent genetic study has evidenced the segregation of such a mutation named FecLL. However, based on litter size (LS) records of FecLL non-carrier ewes, the segregation of a second prolificacy major mutation was suspected in this population. In order to identify this mutation, we have combined case/control genome-wide association study with ovine 50k SNP chip genotyping, whole genome sequencing and functional analyses. A new single nucleotide polymorphism (OARX:50977717T>A, NC_019484) located on the X chromosome upstream of the BMP15 gene was evidenced highly associated with the prolificacy variability (P =1.93E-11). The variant allele was called FecXN and shown to segregate also in the Blanche du Massif Central (BMC) sheep population. In both NV and BMC, the FecXN allele frequency was estimated close to 0.10, and its effect on LS was estimated at +0.20 lamb per lambing at heterozygous state. Homozygous FecXN carrier ewes were fertile with increased prolificacy in contrast to numerous mutations affecting BMP15. At the molecular level, FecXN was shown to decrease BMP15 promoter activity and supposed to impact BMP15 expression in oocyte. This regulatory action was proposed as the causal mechanism for the FecXN mutation to control ovulation rate and prolificacy in sheep.